Implementasi Kebijakan Sertifikasi Guru dalam Meningkatkan Mutu Pembelajaran (study kasus pada SMA Negeri 6 Sigi Kabupaten Sigi) - Riandhana, Taufiq Eka (Center of Education Journal (CEJou), 2022)
The purpose of the study was to determine the implementation of teacher certification policies in improving the quality of learning at SMA Negeri 6 Palolo and the inhibiting, supporting factors and alternative solutions. The basis of the research is a survey, while the type of research is descriptive qualitative which is intended to provide a general description of the object under study. In this study, the authors set the 6 Sigi State Senior High School as the research location. The population in this study was 646 (six hundred and forty six) people. Sampling with purposive sampling technique. Data collection techniques through observation, interviews, questionnaires and documentation. This study uses a qualitative descriptive analysis technique and the results of this study will be presented using tools in the form of frequency tables and percentage tables. The results of this study indicate that communication, bureaucratic structure that causes good input and output so as to produce quality students in the sense of having adequate skills and knowledge after graduating from Palolo 6 Public High School and being able to compete with other schools to enter higher education. However, resources and dispositions that affect the learning process. In this case, the attitude, nature or characteristics of the teacher are not good in terms of obedience and accuracy of entry at the time of teaching so that the quality of learning is of less quality due to the hours of learning that are not in accordance with the specified. Keywords: Policy Implementation, Teacher Certification